ORGANIZATION OF INDEPENDENT WORK STUDENTS OF MASTER OF TELECOMMUNICATION TRAINING PROJECT - Perminova Л.А. (Journal of Information Technologies in Education (ITE), 2013)
The article explains the need to implement active learning of students in the practice of the organization їh homework. In particular, the author proved the rationality of the use of telecommunications projects and use the web in quest of independent study students graduate.